Three Hospital Admissions in 9 Days to Diagnose Azathioprine Hypersensitivity in a Patient With Crohn's Disease. (March 2015) - Mookherjee, Somnath; Narayanan, Maya; Uchiyama, Tomoharu; Wentworth, Kelly L.
Abstract : Azathioprine (AZA) is commonly used as a steroid-sparing immunosuppressive medication for the treatment of immune-mediated disorders including Crohn's disease. There is ample awareness of the more common adverse effects of this drug, including myelosuppression and risk of malignancy. We present a case of a 57-year-old man with fistulizing Crohn's disease who underwent 3 hospital admissions for recurrent fever with an extensive work-up for infection before the diagnosis of AZA hypersensitivity was made. Clinicians should be vigilant for AZA hypersensitivity as a cause of otherwise unexplained fever. Furthermore, in patients with inflammatory bowel disease (IBD), the signs and symptoms of AZA hypersensitivity may overlap with typical findings of inflammatory bowel disease flare.